1994
DOI: 10.1006/jagm.1994.1030
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Routing and Sorting on Fixed-Connection Networks

Abstract: This paper presents a general paradigm for the design of packet routing algorithms for fixed-connection networks. Its basis is a randomized on-line algorithm for scheduling any set of N packets whose paths have congestion c on any bounded-degree leveled network with depth L in O(c + L + log N ) steps, using constant-size queues. In this paradigm, the design of a routing algorithm is broken into three parts: (1) showing that the underlying network can emulate a leveled network, (2) designing a path selection st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
63
0
1

Year Published

1994
1994
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(65 citation statements)
references
References 39 publications
1
63
0
1
Order By: Relevance
“…For the class of leveled networks, Leighton, Maggs, Ranade, and Rao [8] showed that there is a simple on-line randomized algorithm for routing the packets to their destinations within O(c + L + log N) steps, with high probability, where L is the numb e r o f l e v els in the network, and N is the total number of packets.…”
Section: Previous and Related Workmentioning
confidence: 99%
“…For the class of leveled networks, Leighton, Maggs, Ranade, and Rao [8] showed that there is a simple on-line randomized algorithm for routing the packets to their destinations within O(c + L + log N) steps, with high probability, where L is the numb e r o f l e v els in the network, and N is the total number of packets.…”
Section: Previous and Related Workmentioning
confidence: 99%
“…Leveled networks have also been studied in the context of store-and-forward scheduling (with buffers), by Leighton et al [32], where they present an O(C +L+log N) randomized algorithm with constant size buffers. For store-and-forward scheduling, there have been many results on obtaining optimal O(C + D) algorithms for arbitrary networks [31,33,36,40,43].…”
Section: Related Work On Leveled Networkmentioning
confidence: 99%
“…Finally, it is worth pondering the relationship between multicast routing and a form of unicast routing which allows multiple messages sharing a common destination s to be combined into a single message along their way to s [16,10]. In fact, for every instance M of the multicast routing problem in which each message x ∈ M must be delivered from its source s(x) to its various destinations {t 1 (x), t 2 (x), .…”
Section: Introductionmentioning
confidence: 99%
“…However, none of the known algorithms for unicast routing (with combining) provides the basis for an efficient multicast algorithm. For example, the work by [10] is largely concerned with scheduling the movement of packets along pre-selected paths; the path selection techniques employed (largely based on greedy path selection and random intermediate destinations)…”
Section: Introductionmentioning
confidence: 99%